Analysis of Dependence on Oil and Gas, TPT, and Human Development Index (HDI) on Economic Growth and Poverty in Bojonegoro Regency 1995-2024 - Putri Autika Arifin; Joko Hadi Susilo; Moh Saiful Anam (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2025)
This study analyses the influence of Oil and Gas Revenue Sharing Funds (DBH Migas), the Open Unemployment Rate (TPT), the Human Development Index (HDI), and global oil prices on economic growth and poverty in Bojonegoro Regency during the 1995–2024 period. Using annual time-series data and a quantitative approach, the analysis employs the ADF stationarity test, Ordinary Least Squares (OLS), Two-Stage Least Squares (2SLS), the Durbin–Wu–Hausman endogeneity test, and the Toda–Yamamoto causality procedure. The results show that the HDI positively affects economic growth, whereas unemployment and poverty negatively affect growth; however, not all relationships are statistically significant. Oil and Gas DBH and global oil prices are not strong determinants of regional GDP, indicating Bojonegoro's reliance on external factors inherent in the oil and gas sector. In the poverty model, unemployment is the most influential variable, whereas GDP, the HDI, and oil prices do not exhibit significant direct effects. The Toda–Yamamoto causality test reveals causal relationships from HDI to GDP, from unemployment to poverty, and from poverty to HDI, whereas most variable pairs do not exhibit reciprocal causality. Overall, the findings suggest that Bojonegoro's economic development is driven more by improvements in human capital and employment opportunities than by fluctuations in oil and gas revenues.